A 2015 outbreak of flea-borne rickettsiosis in San Gabriel Valley, Los Angeles County, California. - Kimberly Nelson; Alice N Maina; Angela Brisco; Chelsea Foo; Curtis Croker; Van Ngo; Rachel Civen; Allen L Richards; Kenn Fujioka; J Wakoli Wekesa (Public Library of Science (PLoS), 2018)
Although flea-borne rickettsiosis is endemic in Los Angeles County, outbreaks are rare. In the spring of 2015 three human cases of flea-borne rickettsiosis among residents of a mobile home community (MHC) prompted an investigation. Fleas were ubiquitous in common areas due to presence of flea-infested opossums and overabundant outdoor cats and dogs. The MHC was summarily abated in June 2015, and within five months, flea control and removal of animals significantly reduced the flea population. Two additional epidemiologically-linked human cases of flea-borne rickettsiosis detected at the MHC were suspected to have occurred before control efforts began. Molecular testing of 106 individual and 85 pooled cat fleas, blood and ear tissue samples from three opossums and thirteen feral cats using PCR amplification and DNA sequencing detected rickettsial DNA in 18.8% of the fleas. Seventeen percent of these cat fleas tested positive for R. felis-specific DNA compared to under two (<2) percent for Candidatus R. senegalensis-specific DNA. In addition, serological testing of 13 cats using a group-specific IgG-ELISA detected antibodies against typhus group rickettsiae and spotted fever group rickettsiae in six (46.2%) and one (7.7%) cat, respectively. These results indicate that cats and their fleas may have played an active role in the epidemiology of the typhus group and/or spotted fever group rickettsial disease(s) in this outbreak.